(untitled) (International Journal of Food and Nutritional Sciences, 2022)
G-4 (Guanine containing-Quadruplex) is highly specialized non-canonical motif related to Genetic material (DNA). G-4, clearly recognize that its involvement into replication of many cancerous cells, apart from whole central dogma process in cancer-related genes. Hence, targeting G-4 has become a new promising area for anti-cancer drug development. Targeting G4 through low molecular weight molecules targeting the G-4 have been designed, synthesized, verified to immense use against tumor cells, it involves that molecule directly stack to the G-4 non canonical motif. The significance of the G-Quadruplex motif acting as an anti-cancer drug, especially in metastatic cancer, Indeed helicase is an enzymatic protein, which is more specific towards G-4 scaffold, emerging target like helicase in case of G-4 motif is big deal to design specific small scaffold that helps in hacking cancer problem since Elizabeth discovery of G-4.